2016
DOI: 10.1007/s00381-016-3181-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lacosamide “a novel antiepileptic drug” in the early stages of chicken embryo development

Abstract: Based on our data, LCM may cause growth retardation or major congenital malformations. Nevertheless, more extensive investigations of its reliability are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
12
0
2
Order By: Relevance
“…For example, congenital abnormalities such as growth retardation, microcephaly, orofacial defects, and NT damage are associated with AED treatment. Mete et al [6] investigated the effects of LCM on chicken embryo development and observed anencephaly with growth retardation during macroscopic examinations. The present study evaluated whether histological changes occurred at the NT level following LCM treatment and found that, although the NT closed, there were dosedependent increases in proliferating cells and pyknotic cells, and the cells were organized into a compact structure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, congenital abnormalities such as growth retardation, microcephaly, orofacial defects, and NT damage are associated with AED treatment. Mete et al [6] investigated the effects of LCM on chicken embryo development and observed anencephaly with growth retardation during macroscopic examinations. The present study evaluated whether histological changes occurred at the NT level following LCM treatment and found that, although the NT closed, there were dosedependent increases in proliferating cells and pyknotic cells, and the cells were organized into a compact structure.…”
Section: Discussionmentioning
confidence: 99%
“…After 30 h of incubation, the eggs were opened under 4× optical magnification [7][8][9] at Hamburger-Hamilton stage 9 [8] and rinsed with 70% ethanol. Then, a piece of adhesive tape was placed close to the egg air cavity and a small window was opened for the injections [6].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations